Bentuk-bentuk Cyberbullying yang terdapat dalam Drama San Nen A Gumi Karya Shogo Muto - Wijayanti, Ni Kadek Rika; Aryani, Made Ratna Dian; Sari, Ida Ayu Laksmita (Chi'e: Journal of Japanese Learning and Teaching, 2021)
This research is entitled "Forms of Cyberbullying in the Drama San Nen A Gumi by Shogo Muto". The purpose of this study is to describe the forms of cyberbullying in the data source used, namely the drama San Nen A Gumi by Shogo Muto. The method used in this research is the library method, descriptive analysis method and informal method. The theory used consists of two theories, namely the theory of sociology of literature according to Wellek and Warren and the theory of cyberbullying according to Willard. The results showed that there are five forms of cyberbullying, including 1) flaming 'sending fiery messages' 2) harassment 'sending disturbing messages of harassment repeatedly', 3) denigration 'making or spreading slander', 4) impersonation 'disguise', and 5) outing and trickery 'obtaining or spreading secrets from the target by deceit'.